2009
DOI: 10.1177/0731684409103958
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Modulus of Semi-auxetic Unidirectional Fiber Composites

Abstract: In micromechanical modeling of composites, it is well known that the Voigt formula or the rule-of-mixture method gives the most general upper bound estimate of the effective Young's modulus. In this article it is shown that the effective longitudinal Young's modulus of a continuous unidirectional fiber composite significantly exceeds the rule-of-mixture when both constituents possess equal or almost equal Young's moduli and opposing Poisson's ratio signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…It has also been shown that combination of auxetic and conventional materials not only produce in‐between properties, but also properties that are unique to both, such as bi‐layered strip consisting of an auxetic lamina and a conventional lamina that gives significant thickening or thinning depending on the direction of bending 42, and multi‐layered alternating auxetic and conventional laminas that not only exhibit modulus above the direct rule of mixture, but also exceeds the modulus of the stiffer phase 43–48. A similar result was also obtained for the axial modulus of continuous unidirectional fiber composites where the Poisson's ratio of the fiber and modulus possess opposite signs 49. In the case of 3‐ply laminate consisting of isotropic laminas with alternating Poisson's ratio signs, specific conditions lead to auxetic behavior during axial loading but conventional behavior during bending and vice versa 50.…”
Section: Introductionsupporting
confidence: 59%
“…It has also been shown that combination of auxetic and conventional materials not only produce in‐between properties, but also properties that are unique to both, such as bi‐layered strip consisting of an auxetic lamina and a conventional lamina that gives significant thickening or thinning depending on the direction of bending 42, and multi‐layered alternating auxetic and conventional laminas that not only exhibit modulus above the direct rule of mixture, but also exceeds the modulus of the stiffer phase 43–48. A similar result was also obtained for the axial modulus of continuous unidirectional fiber composites where the Poisson's ratio of the fiber and modulus possess opposite signs 49. In the case of 3‐ply laminate consisting of isotropic laminas with alternating Poisson's ratio signs, specific conditions lead to auxetic behavior during axial loading but conventional behavior during bending and vice versa 50.…”
Section: Introductionsupporting
confidence: 59%
“…The extent of anisotropy increases when the array goes to the extremes, thereby leading to extreme negative Poisson’s ratios. The results from this paper, in conjunction with earlier works on auxetic beams [40,41], auxetic rods [42,43,44], auxetic plates [45,46,47,48,49,50,51,52], auxetic shells [53,54], auxetic composites [55,56,57,58,59,60,61,62] and 2D metamaterial structures [63,64], would avail more design options for the engineer in developing novel load bearing materials and structures.…”
Section: Discussionsupporting
confidence: 71%
“…Interlacing effects from the auxetic and conventional materials have been shown to give interesting properties in bi-layer [ 49 , 50 ], tri-layer [ 51 , 52 ], and multi-layered systems [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], and continuous unidirectional fiber composites [ 61 ]. One category of auxetic structural element is that of rods possessing circular or elliptical cross-sections with auxetic and conventional materials alternated in concentric [ 62 , 63 ], angular [ 64 ], and helical [ 65 ] directions.…”
Section: Introductionmentioning
confidence: 99%